Mechanochemical Solvent‐Free Conditions for the Synthesis of Pillar[5]arene‐Containing [2]Rotaxanes. Issue 21 (1st March 2019) - Holler, Michel; Stoerkler, Timothée; Louis, Alexandra; Fischer, Fanny; Nierengarten, Jean‐François
Abstract : Pillar[5]arene‐containing [2]rotaxanes have been efficiently prepared under solvent‐free conditions. Specifically, solid‐to‐solid ball‐milling of primary or secondary amine reagents with the inclusion complex resulting from the association of dodecanedioyl dichloride and a pillar[5]arene derivative provided the corresponding diamide [2]rotaxanes in good to excellent yields. Importantly, [2]rotaxanes difficult or even impossible to prepare under classical reaction conditions in solution, are now easily obtained. Abstract : Solid‐to‐solid ball‐milling of amine reagents and the inclusion complex resulting from the association of dodecanedioyl dichloride and a pillar[5]arene derivative provided the corresponding diamide [2]rotaxanes in good to excellent yields.